Modeling the Evolution of Aquatic Organisms in Dynamic River Basins. Issue 9 (14th September 2020) - Stokes, Maya F.; Perron, J. Taylor
Abstract: Rivers are conduits for aquatic organisms and host an exceptional number of species. Over geologic time, rivers and the aquatic organisms that live in them are subject to changes in topography that can alter where rivers flow. Differences in erosion rates across drainage divides cause some river basins to grow and others to shrink. Occasionally, rivers are abruptly rerouted by river captures that create both new dispersal corridors and barriers for aquatic organisms. These changes in habitat connectivity can lead to the evolution of new species, which has prompted suggestions that river captures may be a mechanism to produce high freshwater biodiversity. We test this hypothesis by building a model, Bio‐SLANT (Biodiversity on Simulated LAndscapes using Neutral Theory). Bio‐SLANT couples a computational landscape model that simulates river basin reorganization to a macroevolutionary model that simulates the dispersal, speciation, and extinction of organisms. We first show that modeled basin area exerts a primary control on within‐basin species richness due to the species‐area relationship. We then describe the effects of drainage area exchange between river basins. River capture increases species richness, but only temporarily, whereas elevated rates of speciation and extinction provide a persistent biological record of river network reorganization. When river captures are frequent, speciation rates increase more than extinction rates, resulting in a positive diversification rate under most of the biological parameters tested. We explore the implications of our results for species richness in landscapes with basins of different relative sizes and for diversification in tectonically active and inactive settings. Key Points: A coupled model of macroevolution and river network reorganization is used to investigate the effects of river capture on aquatic organisms River captures lead to transient increases in species richness An increased diversification rate is a persistent biological record of river capture